Mutant of Vesicular Stomatitis Virus Which Allows Deoxyribonucleic Acid Synthesis and Division in Cells Synthesizing Viral Ribonucleic Acid - Farmilo, A. J. (1972)
Some temperature-sensitive mutants of vesicular stomatitis virus were tested for their ability to block the initiation of deoxyribonucleic acid (DNA) synthesis and division in serum-stimulated hamster embryo fibroblasts at the nonpermissive temperature. Although the parental strain blocked these processes, one particular mutant allowed essentially normal DNA synthesis and division. By autoradiography, it was shown that individual cells infected with this mutant could synthesize viral ribonucleic acid and at the same time initiate DNA synthesis and divide. Cells infected with such conditional defective mutants appear to be suitable for studies on the effects of persistent viral infections on molecular and cellular functions in proliferating cell populations.